PENINGKATAN HASIL BELAJAR BIOLOGI DENGAN PENERAPAN MODEL KOOPERATIF TIPE STAD PADA SISWA KELAS X-F SMA NEGERI 1 TANGEN SRAGEN TAHUN PELAJARAN 2013/2014 - Nanang Riyadi; Meti Indrowati; Bowo Sugiharto (Universitas Sebelas Maret, 2015)
This research aimed to improve biology learning achievement with STAD type of cooperative model application in the X-F graders of SMA Negeri 1 Tangen Sragen in the school year of 2013/2014. This study was a classroom action research conducted in 2 cycles, each of wich consisted of planning, acting, observing, and reflecting. The indicator of achievement in this research was the student’ learning output improving to 72 from KKM (Minimum Passing Criterion) of 70. The data was analyzed descriptively qualitatively and statistically descriptively. The data validation was carried out using observer triangulation. The results of research showed that the biology learning achievement of 62,78 in pre-cycle could be increased with the application of STAD learning model to 70,52 in cycle 1 and 73,02 in cycle 2. The conclusion that could be drawn was that the application of STAD learning model could improve the biology learning achievement of the X-F graders of SMA Negeri 1 Tangen Sragen in the school year of 2013/2014. Keywords: Student Teams-Achievement Divisions (STAD), Biology Learning Achievement.